Curriculum and teaching dialogue. Volume 17, numbers 1 and 2 - Flinders, David J.; Moroye, Christy M. (Curriculum & teaching dialogue, 2015)
Curriculum and Teaching Dialogue (CTD) is a publication of the American Association of Teaching and Curriculum (AATC), a national learned society for the scholarly field of teaching and curriculum. The field includes those working on the theory, design and evaluation of educational programs at large. At the university level, faculty members identified with this field are typically affiliated with the departments of curriculum and instruction, teacher education, educational foundations, elementary education, secondary education, and higher education. CTD promotes all analytical and interpretive approaches that are appropriate for the scholarly study of teaching and curriculum. In fulfillment of this mission, CTD addresses a range of issues across the broad fields of educational research and policy for all grade levels and types of educational programs.